Adaptive Fuzzy Sliding Mode Control for Translational Oscillator With Rotating Actuator: A Fuzzy Model - Tiebin Wu; Weihua Gui; Dong Hu; Chenglong Du (IEEE Access, 2018)
This paper is concerned with the issue of adaptive fuzzy sliding mode control for fuzzy underactuated translational oscillator with rotating actuator (TORA). Since the system considered in this paper is accompanied by strong inputs coupling and nonlinear characteristics, the feedback decoupling and fuzzy technique are introduced to establish a linear fuzzy underactuated TORA system. The two-order fuzzy sliding surface with adaptive parameters is designed, where the adaptive control is introduced to adjust the parameters of sliding surface such that the system performance could be improved. The sliding mode control law is synthesized to guarantee the sliding mode dynamics to be asymptotically stable and robust, and the reachability analysis is presented to ensure that the system trajectories can be driven onto the sliding mode surface and remain there for the subsequent time. Simulation results are provided to compare with the existing results and validate the effectiveness and feasibility of the proposed scheme.